Using Grounded Theory Method in Information Systems: The Researcher as Blank Slate and Other Myths - Urquhart, Cathy; Fernández, Walter (Journal of information technology, 2013)
The use of grounded theory method (GTM) as a research method in information systems (IS) has gradually increased over the years as qualitative research in general has become more prevalent. The method offers a systematic way to generate theory from data, but is rarely used to its full potential in IS as a number of myths and misunderstandings about GTM prevent researchers from getting the full potential out of the method. To address this problem, we advance the general level of knowledge of GTM. We clarify aspects of the method that are often misunderstood by novice users or casual observers and provide guidance to address common problems. Exemplars from the IS literature are used to illustrate the concepts and to promote the informed use of the methodology. By doing so, this paper will contribute to improving the use of the method and to the quality and dissemination of grounded theory research outcomes.